A comparative study of tree-based models for churn prediction : a case study in the telecommunication sector - Kandel, Ibrahem Hamdy Abdelhamid (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research e CRM